The Effect of Islamic Corporate Governance, Islamic Corporate Social Responsibility, Corporate Zakat, and Intellectual Capital on Financial Performance - Aminatuzzuhriyeh Aminatuzzuhriyeh; Millatina Hanifah (Journal of Accounting and Auditing, 2026)
Purpose – This research aims to obtain empirical evidence about the influence of Islamic Corporate Governance (ICG), Islamic Corporate Social Responsibility (ICSR), Corporate Zakat, and Intellectual Capital on Financial Performance. Design/methodology/approach – This study uses a quantitative method with a secondary data obtained from financial reports and annual reports of Islamic commercial banks (ICBs) in Indonesia during the period 2022-2024. Data analysis was performed using EViews Version 9 software. Findings – The study identifies that Islamic Corporate Social Responsibility (ICSR) and Intellectual Capital show positive and significant, results Islamic Corporate Governance (ICG) has a positive but insignificant effect, in contrast to Corporate Zakat, which shows an insignificant effect with negative results of Financial performance. Research limitations/Implications – This study discusses the effect of Islamic Corporate Governance (ICG), Islamic Corporate Social Responsibility (ICSR), corporate Zakat, and Intellectual Capital on the financial performance of Islamic Commercial Banks (ICBs) in the period 2022-2024. The implications of this study are limited to Islamic Commercial banks in 2022-2024, so it is necessary to use a broader sample in the Islamic banking sector and add other variables to be able to describe more comprehensive factors that influence the financial performance of Islamic banking. JEL : G21, G34, M14, Z12, O34.